Public Consultations and Hearings: A Vital Form of Public Participation in Legislative Activity - Saida Abdimalikova (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2025)
This thesis examines the legal and institutional framework for public participation, the process and benefits of consultations and hearings, and the challenges faced in ensuring inclusivity and effectiveness. It highlights how these processes promote transparency, accountability, informed decision-making, and social cohesion while fostering greater trust in the government.